Cinnamon and Gotu Kola Supplementation to Produce High Antioxidant and Low Cholesterol of Quail Pectoral Meat - Sunarno, Sunarno; Zubaedah, Siti; Rini, Almalina Nabila Sulistyo; Sekarsari, Eryanti; Rahadian, Rully (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Cholesterol in quail meat is one of the factors causing consumers to control consumption of quail meat. On the other hand, the antioxidant content in quail meat could attracts the consumers. Cinnamon (Cinnamomum sp.) bark and gotu kola (Centella asiatica) leaves are medicinal plants that contain many polyphenol compounds. The objective of this study was to obtain the most optimum formula made from cinnamon and gotu kola as a feed supplement to produce the quail meat which has low cholesterol but rich in antioxidants. This study used a completely randomized design which consisting of six groups with three replications. The six groups included one control (P0), 5 treatments consisted of 5% cinnamon (P1), 5% gotu kola (P2), combination of cinnamon and gotu kola powder with ratio 5%:5% (P3), 5%:10% (P4) and 10%:5% (P5). The results showed that food supplements made from cinnamon bark and gotu kola leaves could increase the body weight, antioxidant levels, and reduce cholesterol levels in quail meat. Cinnamon as feed supplement with a concentration of 5% or a combination of cinnamon and gotu kola with a ratio of 5%: 10% provided the best effect on antioxidants and cholesterol level in meat. The use of cinnamon and gotu kola supplementation to produce high antioxidant and low cholesterol of quail met have not studied yet. The result of the study would be beneficial for developing the healthy, safe and good quality of quail meat.